Modelling the alumina abundance of oxygen-rich evolved stars in the Large Magellanic Cloud. Issue 1 (12th March 2014) - Jones, O. C.; Kemper, F.; Srinivasan, S.; McDonald, I.; Sloan, G. C.; Zijlstra, A. A.
Abstract: In order to determine the composition of the dust in the circumstellar envelopes of oxygen-rich asymptotic giant branch (AGB) stars, we have computed a grid of modust radiative-transfer models for a range of dust compositions, mass-loss rates, dust-shell inner radii and stellar parameters. We compare the resulting colours with the observed oxygen-rich AGB stars from the SAGE-Spec Large Magellanic Cloud (LMC) sample, finding good overall agreement for stars with a mid-infrared excess. We use these models to fit a sample of 37 O-rich AGB stars in the LMC with optically thin circumstellar envelopes, for which 5–35 μm Spitzer infrared spectrograph (IRS) spectra and broad-band photometry from the optical to the mid-infrared are available. From the modelling, we find mass-loss rates in the range ∼8 × 10 −8 –5 × 10 −6  M⊙  yr −1, and we show that a grain mixture consisting primarily of amorphous silicates, with contributions from amorphous alumina and metallic iron, provides a good fit to the observed spectra. Furthermore, we show from dust models that the AKARI [11]−[15] versus [3.2]−[7] colour–colour diagram is able to determine the fractional abundance of alumina in O-rich AGB stars.